Role of mTOR inhibitor in the cellular and humoral immune response to a booster dose of SARS-CoV-2 mRNA-1273 vaccine in kidney transplant recipients - Pérez-Flores, Isabel; Juarez, Ignacio; Aiffil Meneses, Arianne S.; Lopez-Gomez, Ana; Romero, Natividad Calvo; Rodriguez-Cubillo, Beatriz; Moreno de la Higuera, María Angeles; Peix-Jiménez, Belen; Gonzalez-Garcia, Raquel; Baos-Muñoz, Elvira; Vilela, Ana Arribi; Gómez Del Moral, Manuel; et al. (Frontiers in Immunology, 2023)
Background: Immunocompromised patients have an increased risk of developing severe COVID disease, as well as a tendency to suboptimal responses to vaccines. The objective of this study was to evaluate the specific cellular and humoral adaptive immune responses of a cohort of kidney transplant recipients (KTR) after 3 doses of mRNA-1273 vaccine and to determinate the main factors involved. Methods: Prospective observational study in 221 KTR (149 non infected), 55 healthy volunteers (HV) and 23 dialysis patients (DP). We evaluated anti-spike (by quantitative chemiluminescence immunoassay) and anti-nucleocapsid IgG (ELISA), percentage of TCD4+ and TCD8+ lymphocytes producing IFNγ against S-protein by intracellular flow cytometry after Spike-specific 15-mer peptide stimulation and serum neutralizing activity (competitive ELISA) at baseline and after vaccination. Results: Among COVID-19 naïve KTR, 54.2% developed cellular and humoral response after the third dose (vs 100% in DP and 91.7% in HV), 18% only showed cell-mediated response, 22.2% exclusively antibody response and 5.6% none. A correlation of neutralizing activity with both the IgG titer (r=0.485, p<0.001) and the percentage of S-protein–specific IFNγ–producing CD8-T cells (r=0.198, p=0.049) was observed. Factors related to the humoral response in naïve KTR were: lymphocytes count pre-vaccination >1000/mm3 [4.68 (1.72-12.73, p=0.003], eGFR>30 mL/min [7.34(2.72-19.84), p<0.001], mTOR inhibitors [6.40 (1.37-29.86), p=0.018]. Infected KTR developed a stronger serologic response than naïve patients (96.8 vs 75.2%, p<0.001). Conclusions: KTR presented poor cellular and humoral immune responses following vaccination with mRNA-1273. The immunosuppression degree and kidney function of these patients play an important role, but the only modifiable factor with a high impact on humoral immunogenicity after a booster dose was an immunosuppresive therapy including a mTOR inhibitor. Clinical trials are required to confirm these results.